Handbook of surgical consent - Nair, Rajesh; Holroyd, David J. (Oxford ; New York : Oxford University Press, 2012)
"Patients have an ethical and legal right to decide whether or not to undergo medical or surgical intervention, and it is vital that the healthcare professional is equipped to advise and inform the patient appropriately so they can make this important decision. Gaining fully informed consent is a structured process and often not fully taught in medical schools. It is, however, essential that the professional gaining consent is able to perform the procedures, and be fully aware of the pitfalls and risks involved along every step of the way. Written for surgical trainees, but useful for all healthcare professionals who gain medical and surgical consent, the Handbook of Surgical Consent is a new and valuable tool, written by experts, offering practical guidance in the principles of consent, alongside procedure-specific information on the risks and benefits. It will help improve the quality and content of verbal and written consent in surgical practice, assist the reader in discussing treatments with patients, improving understanding and encouraging good consent practice. The handbook is written in a unique format mirroring the structure of the UK Department of Health consent form, which allows for easy reference when consenting a patient directly. Comprehensively covering all surgical specialties, the Handbook of Surgical Consent includes chapters on obstetrics, gynaecology, ENT, and ophthalmology, and covers subspecialties now normally covered in surgical rotations. The handbook is concise and easy to understand, and is fully illustrated to give useful detail on anatomy, techniques or complications that can be shown to patients at the bedside to enhance knowledge and understanding during the consent process"--
Machine generated contents note: -- 1. General principles of consent, R.A.Wheeler, R. Nair, D. Holroyd -- 2. General surgical procedures, S. Sangal, A. Holroyd, H. Sheth, D. Francis -- 3. Colorectal surgery, R.P. Stevenson, A.M. Armstrong -- 4. Vascular surgery, N. Ashraf, A. Sud, J. Menon -- 5. Endocrine surgery, F. Pakzad, F. Palazzo -- 6. Breast surgery, F. Pakzad, A. Sud, M. Miahmeed -- 7. Hepato-pancreatico-biliary surgery, H. Sheth, A. Abraham -- 8. Upper gastrointestinal and bariatric surgery, C. Bryant, A. Chaudry, S.F. Hughes -- 9. Transplantation surgery, A. Bagul, M. Nicholson -- 10. Laparoscopic surgery, S. Kumar, P. Jethwa, D. Francis -- 11. Urological surgery, R. Nair, D. Holroyd, G. Webster -- 12. Orthopaedic surgery, T. Hester, M. Ramachandran -- 13. Plastic surgery, S. Naji, M. James -- 14. Ear, nose, and throat surgery, A. Alli, A. Singh -- 15. Paediatric surgery, R.E. Hill, S.B. Hill, R.A. Wheeler -- 16. Neurosurgery, D. D'Aquino, B. White, I. Robertson -- 17. Cardiothoracic surgery, O. Lyons, J. Roxburgh, H. Raubenheimer, J. King -- 18. Oral and maxillofacial surgery, C. Robertson, S. Matthews -- 19. Ophthalmologic surgery, K. Patel, L. Ogunbowale, B. Chang -- 20. Obstetrics and gynaecology, N. Suff, J. Farren, M Parisaei.
Includes bibliographical references and index.
Keywords: Informed Consent; Surgical Procedures, Operative; Risk Assessment; Handbooks